2020
DOI: 10.1002/jrsm.1398
|View full text |Cite
|
Sign up to set email alerts
|

Comparing machine and human reviewers to evaluate the risk of bias in randomized controlled trials

Abstract: Background: Evidence from new health technologies is growing, along with demands for evidence to inform policy decisions, creating challenges in completing health technology assessments (HTAs)/systematic reviews (SRs) in a timely manner. Software can decrease the time and burden by automating the process, but evidence validating such software is limited. We tested the accuracy of RobotReviewer, a semi-autonomous risk of bias (RoB) assessment tool, and its agreement with human reviewers.Methods: Two reviewers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, in areas with a degree of subjectivity (e.g. determining whether a study is at risk of bias), the subjective opinion of an expert human may be still more reliable than a machine’s decision (Armijo‐Olivo, Craig, & Campbell, 2020; Marshall & Wallace, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, in areas with a degree of subjectivity (e.g. determining whether a study is at risk of bias), the subjective opinion of an expert human may be still more reliable than a machine’s decision (Armijo‐Olivo, Craig, & Campbell, 2020; Marshall & Wallace, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, the Cochrane RoB 1.0 tool was updated and replaced by the RoB 2.0 tool 55. RobotReviewer’s accuracy has been tested by the developers50 and three independent research teams 7 56 57. The authors reported moderate agreement between the tool and human reviewers (range: 46%–100%) 7 50 56 57.…”
Section: Specific Recommendations For Supportive Software Use During ...mentioning
confidence: 99%
“…RobotReviewer’s accuracy has been tested by the developers50 and three independent research teams 7 56 57. The authors reported moderate agreement between the tool and human reviewers (range: 46%–100%) 7 50 56 57. RobotReviewer7 50 56 57 can be helpful in supporting a reviewer’s RoB assessment by providing an automated assessment of four out of seven domains, which can save time and costs.…”
Section: Specific Recommendations For Supportive Software Use During ...mentioning
confidence: 99%
“…Following the Cochrane Risk of Bias tool for randomised controlled trials (RCTs), RobotReviewer provides an overall assessment of risk of bias, and extracts supporting sentences from PDF les of full-text reports 67 . RobotReviewer was used in further ve studies 18,99,103,119,137 . One paper assessed the risk of bias in preclinical animal studies, comparing various techniques including recurrent neural networks with attention, convolutional neural networks and BERT 150 .…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%